KEMAMPUAN SISWA MAN 2 PEKALONGAN DALAM MENULIS TEKS DESKRIPTIF DAN RECOUNT BAHASA INGGRIS (Jurnal Penelitian, 2012)
The purpose of this study was to find out how well the descriptive text and recount text written by the students is and how communicative goals in a descriptive text appear. The results showed that the students of MAN 2 Pekalongan, in general, are able to write recount and descriptive text, although there are many grammatical mistakes (grammatical errors) or word-order (making the word) made in their writings. It was also found that the implementation of learning English based on the 2006 curriculum which used the GBA (Genre Based Approach) had weaknesses, such as the problem of lack of learning tenses and how to compose a sentence in English.
Keywords: teks deskriptif, teks recount, gramatical mistake, word- order